The State Budget in the Digital Age: Opportunities and Threats - Artemyeva, I. O.; Yakovenko, M. A. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The article is devoted to the changes in national budgets under the influence of digitization. The aim of the study is to determine the opportunities and threats posed by the development of the digital economy in the field of formation and implementation of national budgets, and to outline possible ways to effectively balance the potential benefits against the risks and limitations. This article argues that digitalization reshapes public finance. The main benefits of digital transformations such as increase of the tax base, optimization and transparency of government revenues and spending, fiscal savings, better tax administration, delivery of public services, administration of social programs, cutting of bureaucratic inefficiencies are considered. The most important risks and challenges, including privacy concerns, new avenues for fraud and evasion and institutional constraints are outlined. The article describes what governments should do to make benefits outweigh the risks. Taking full advantage of the opportunities of digitalization can require government to develop new skills. The article also stresses that each country needs to chart its own path to national budget digitalization that must depend on its own circumstances. It is concluded that developing countries may be able to leapfrog directly to the latest digital technologies and more sophisticated policies bypassing the intermediate stages.